1985
DOI: 10.1002/pssb.2221320239
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Power Due to Small Polaron Hopping Motion in Disordered Systems

Abstract: A theory is developed of the thermoelectric power associated with electronic phonon-assisted hopping motion between energetically inequivalent sites with different electron-lattice interaction parameters. The general results are applied to the high-temperature small polaron hopping case.Comparison is made with other theories.Es wird eine Theorie der mit elektronischer, phononenunterstiitzter Hoppingbewegung zwischen energetisch nichtiiquivalenten Platzen mit unterschiedlichen Elektron-Gitter-Wechselwirkungspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 11 publications
(1 reference statement)
0
11
0
1
Order By: Relevance
“…The knowledge of <m|V|n>, permits the evaluation of the "microscopic" small polaron velocity operator [64,65],…”
mentioning
confidence: 99%
“…The knowledge of <m|V|n>, permits the evaluation of the "microscopic" small polaron velocity operator [64,65],…”
mentioning
confidence: 99%
“…We found previously [20,211, that good results are obtained if one uses the model of Triberis and Friedman [23] and Triberis [24]. They found that in the high temperature low temperatures the conductivity should follow rather the exp [ -( T0/T)1'4] dependence [25].…”
Section: Epr Studiesmentioning
confidence: 87%
“…The knowledge of < m|V |n >, permits the evaluation of the "microscopic" small polaron velocity operator [34,35],…”
Section: Generalized Molecular Crystal Modelmentioning
confidence: 99%